2017
DOI: 10.3847/1538-4357/aa79f1
|View full text |Cite
|
Sign up to set email alerts
|

Submilliarcsecond Optical Interferometry of the High-mass X-Ray Binary BP Cru with VLTI/GRAVITY

Abstract: We observe the high-mass X-ray binary (HMXB) BP Cru using interferometry in the near-infrared K band with VLTI/GRAVITY. Continuum visibilities are at most partially resolved, consistent with the predicted size of the hypergiant. Differential visibility amplitude ( V 5% D| |) and phase ( 2 f D~) signatures are observed across the He I 2.059 m m and Brγ lines, the latter seen strongly in emission, unusual for the donor star's spectral type. For a baseline B 100 m, the differential phase rms 0 . 2  corresponds … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Additionally, modelling of the X-ray absorption column as a function of orbital phase supports this scenario (Leahy & Kostka 2008). Finally, the presence of the stream has been confirmed directly through near-IR interferometry (Waisberg et al 2017), thus this interpretation appears to be well justified. In this model, the two peaks in the orbital light curve of the source are attributed to the passage of the NS through the stream: the NS overtakes the stream slightly before periastron and is overtaken by the stream at the apastron (Leahy & Kostka 2008).…”
Section: Discussionmentioning
confidence: 59%
“…Additionally, modelling of the X-ray absorption column as a function of orbital phase supports this scenario (Leahy & Kostka 2008). Finally, the presence of the stream has been confirmed directly through near-IR interferometry (Waisberg et al 2017), thus this interpretation appears to be well justified. In this model, the two peaks in the orbital light curve of the source are attributed to the passage of the NS through the stream: the NS overtakes the stream slightly before periastron and is overtaken by the stream at the apastron (Leahy & Kostka 2008).…”
Section: Discussionmentioning
confidence: 59%
“…Comparison to template spectra indicates that emission in He i 2.059µm and Brγ is atypical for supergiants but consistent with early-B hypergiants , 2014b, Waisberg et al 2017). Consequently we classify these stars as B0-1 Ia + (qF381, LHO77), B1-2 Ia + (LHO29, -96, -110, and -146) and B2-3 Ia + (LHO100).…”
Section: B Hypergiantsmentioning
confidence: 66%
“…spectral resolution and S/N data from Hanson et al (1996) to infer trends in spectral morphologies for supergiants in this range. No one publication presents classification criteria for OB hypergiants; for early-to mid-O hypergiants we utilise Hanson et al (2005) and Clark et al (2018), while spectra and analysis of late-O/early-B hypergiants are provided by Clark et al (2012Clark et al ( , 2014b and Waisberg et al (2017). Representative spectra of LBVs in both hot-and cool-phases are provided by , Clark et al (2003Clark et al ( , 2005bClark et al ( , 2009aClark et al ( , 2011 and Oksala et al (2013).…”
Section: Methodsmentioning
confidence: 99%
“…The stream origin is associated with tidal interactions, and the observed peaks in the orbital light curve are attributed to crossings of the stream by the pulsar near the periastron and apastron. Spectral analysis of the optical companion found the evidence for such a spiral-type stream in this system (Kaper et al 2006), moreover, later mid-infrared interferometry confirmed the presence of the stream in the system (Waisberg et al 2017). The X-ray spectrum of GX 301−2 has been reported to exhibit two absorption features at 34 and 51 keV (Fürst et al 2018) interpreted as Cyclotron Resonant Scattering Features (CRSFs), although earlier investigations found a single pulsephase-dependent feature around 30-50 keV (Kreykenbohm et al 2004;La Barbera et al 2005), so there is some ambiguity in interpretation of the spectrum.…”
Section: Introductionmentioning
confidence: 72%